A time series analysis system using visual operations - Yoshikazu Yamamoto; Junji Nakano (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
We design and implement a prototype time series analysis system named TISAS for fully using modern graphical user interface technologies. An object oriented approach is adopted to represent data, statistics and models as instance objects and to visualize them by icons on the screen arranged as a tree for recording the analysis process clearly. When we point an icon which represents an object we want to handle, a pop-up menu, whose items are statistical procedures available for the object, appears. The operation that we select an appropriate procedure from the menu, produces a new object as a result and an icon on the screen to record the history of the analysis. As we can perform almost all statistical analysis on a tree of icons visually and directly following situation sensitive menus by simple mouse operations, GUI of TISAS is easy to use for many users, and is useful for preventing trivial misuse.
urn:nbn:de:kobv:11-10047389
Keywords: 330; graphical user interface; object oriented approach; situationsensitive menu; TIMSAC package